Инактивация центросом в митозе лазерным микрооблучением - Воробьев, И.А.; Драчев, В.А.; Ченцов, Ю.С. (Биополимеры и клетка, 1988)
Облучение центросом в профазе и ранней прометафазе приводит к остановке клеток в митозе. Такое же облучение в поздней прометафазе, метафазе и анафазе не влияет на ход митоза. Ультраструктура облученных центросом не отличается от нормальной, рост микротрубочек от них продолжается. Предполагается, что для нормального завершения митоза необходимо функционирование центросом до стадии прометафазы включительно. Опромінення центросом у профазі та ранній прометафазі призводить до зупинки клітин у мітозі. Таке ж опромінення у пізній прометафазі, метафазі і анафазі не впливає на хід мітозу. Ультраструктура опромінених центросом не відрізняється від нормальної, ріст мікротрубочок від них продовжується. Передбачається, що для нормального завершення мітозу необхідне функціонування центросом до стадії прометафази включно. Centrosomcs of rat kangaroo kidney cells (PtKi) were irradiated with an argon laser microbeam at different stages of mitosis. Microirradiation of one of the centrosomes at prophase resulted in a delay of cells at metaphase. Then the irradiated cells passed directly to interphase. The same microirradiation at the early prometaphase caused irregular cytokinesis without chromosome separation. Microirradiation at late prometaphase and at metaphase did not affect the later stages of mitosis. The electron microscopic studie did not reveal any differences between the irradiated and control centrosomes The data obtained show that centrosomes are not only the microtubule-organizing centre but they also control the processes of cytokinesis, reorganization of chromosomes, etc.